2018
DOI: 10.1080/21645515.2018.1458807
|View full text |Cite
|
Sign up to set email alerts
|

Strategies implemented to address vaccine hesitancy in France: A review article

Abstract: Vaccination has been identified many decades ago as an effective means to prevent several diseases. However, in France, there is an emergence of vaccine hesitancy, that has caused a reduction of vaccination coverage rates. This issue reduces the effectiveness of the immunization process, and represents a real threat to public health that should be urgently addressed. The purpose of this review is to present actions that have been taken to fight against vaccine hesitancy and thus enhance vaccine uptake. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 53 publications
(52 reference statements)
2
20
0
5
Order By: Relevance
“…Previous studies have shown the importance of societal disagreements and antivaccine groups mainly associated with vaccine hesitancy or resistance [22][23][24]. This has been the main concern even in our study.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have shown the importance of societal disagreements and antivaccine groups mainly associated with vaccine hesitancy or resistance [22][23][24]. This has been the main concern even in our study.…”
Section: Discussionmentioning
confidence: 51%
“…An informative platform on the immunisation process may also be of great benefit to both the public and HCPs, and suggestions have already been made for the development of a platform similar to the Swiss INFOVAC academic network [ 40 , 41 ]. Such a platform would be a huge outlet for questions on the immunisation process as well as general queries regarding vaccinations, such as previous, non-COVID-19 rollouts and details of existing programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Controvérsias relacionadas a vacinas surgiram na França desde o início da década de 1990 motivadas pela presença de adjuvantes nas vacinas, como no caso do hidróxido de alumínio e a sua suposta ligação com essa enfermidade (Fokoun, 2018). Estão na base de muitos dos argumentos que sustentam os movimentos antivacinas ao vincularem as vacinas a doenças, entretanto, não há consenso ou base científica sólida que sustente que a aplicação de vacinas que contêm alumínio possa representar algum risco para a saúde (WHO, 2008).…”
Section: Discussionunclassified